Taxonomic changes in Scirtothrips species (Thysanoptera: Thripidae) from México - Rodríguez-Arrieta, Jesús Alexander; Cambero-Campos, Octavio Jhonathan; González-Hernández, Héctor (Zootaxa, 2024)
The twelve species of Scirtothrips known from México are difficult to identify. We present new updates for defining Scirtothrips in that country. The species were re-evaluated using specimens from the National Insect Collection at IBUNAM, México. Visual comparisons of the Scirtothrips holotypes and paratypes were completed and contrasted to the current nomenclature of Central and North America taxa. We proposed synonymy of seven species, but the genus retains the twelve species officially reported in México herein. Scirtothrips citri, Scirtothrips perseae and Scirtothrips dorsalis are crop pests usually recorded. An updated key was developed to identify the Scirtothrips spp. in México.